Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

I have two functions $f(x)$ and $g(x)$ with $D = [0..1]$ and both $f:D \to D$ and $g:D \to D$. Now I have a third function $h(x)$ with $h : D \to D$ defined as $h(x) = a*f(x) + b*g(x)$.

Is it somehow possible do build $h^{-1}(x)$ in this case given I already know $f^{-1}$ and $g^{-1}$.

I did not manage to go any further than $x = f^{-1}(\frac{y-b*g(x)}{a})$ but of course the $g(x)$ in there is my problem.

I would assume that it is not possible to solve this entirely but I am lacking proof for that assumption.

If I would like to approximate the result and would go for Newton's method this would probably be a nightmare as well shooting for $0 = f^{-1}(\frac{y-b*g(x)}{a}) - x$ so any suggestion is welcome.

share|improve this question
1  
Regarding your last sentence, why not apply Newton's method to $f(x) + g(x) - y = 0$ instead of to that complicated expression? –  Rahul Aug 26 '11 at 10:24

1 Answer 1

up vote 4 down vote accepted

No, there is no easy way to go from $f^{-1}$ and $g^{-1}$ to $(f + g)^{-1}$.

For example, take $f(x) = x$ and $g(x) = \log x$, both of which have elementary inverses. However, $h(x) = f(x) + g(x) = x + \log x$ has the inverse $h^{-1}(x) = W(e^x)$, where $W$ is the Lambert W function which cannot be expressed in terms of elementary functions.

Another example: $f(x) = x$ and $g(x) = x^5$. The inverse of $h(x) = x + x^5$ can only be expressed in terms of the Bring radical.

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.